A new norsesquiterpene from the roots of Polyalthia laui. Issue 14 (18th July 2017) - Yu, Zhang-Xin; Zhuo, Ming-Ye; Li, Xiao-Bao; Fu, Yan-Hui; Chen, Guang-Ying; Song, Xiao-Ping; Han, Chang-Ri; Song, Xin-Ming; Fan, Qi-Jing
Abstract: One new norsesquiterpene polyalone A (1 ), and one new natural product 9-keto-cyclocolorenone (2 ), along with three known analogues (3–5 ) were isolated from the roots of Polyalthia laui . Their structures were elucidated by the detailed analysis of comprehensive spectroscopic data. All compounds were evaluated for their cytotoxic activities and antibacterial activities. Abstract :